Case of Hypercalcemia Secondary to Hypervitaminosis A in a 6-Year-Old Boy with Autism. (11th September 2011) - Vyas, Arpita Kalla; White, Neil H.
Abstract : Vitamin A intoxication secondary to over-the-counter nutritional supplements and from its use in acne treatment has been described. However, there have been very few case reports of chronic hypervitaminosis A leading to hypercalcemia in the pediatric population. This paper describes a boy with hypercalcemia secondary to chronic vitamin A intoxication in the context of vitamin A usage for therapy of autism. In addition to discontinuation of vitamin A, hyperhydration, and furosemide, the hypercalcemia in this patient required the use of prednisone and pamidronate to normalize the calcium.